Pengaruh Workload, Work Environment Terhadap Turnover Intention Melalui Work Stress Sebagai Variabel Intervening Pada Pekerja Generasi Z Kabupaten Demak - Ana soraya; Sjahirul Alim, Muchammad Rully; Salma Ida, Luluk (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the influence of workload and work environment on turnover intention among Generation Z employees in Demak Regency, with work stress serving as an intervening variable. A quantitative approach was employed using a survey of 100 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that workload significantly increases work stress and turnover intention, whereas a supportive work environment reduces both. Work stress positively affects turnover intention and mediates the relationships between workload, work environment, and turnover intention. These findings highlight the importance of workload management and a conducive work environment to improve employee retention.